A Review on the Application of Poly(amidoamine) Dendritic Nano-polymers for Modification of Cellulosic Fabrics - Zolriasatein, Ali A. (Recent Innovations in Chemical Engineering, 2020)
Dendritic nano-polymers are recently used in medical and industrial applications. Cationic dendritic polymers can be used for the modification of anionic cellulose fibers. This review deals with the chemical modification of cellulosic fibers with poly(amidoamine) type dendritic polymers. It has been shown that after modification, the physical and mechanical properties including moisture regain, breaking strength, breaking elongation, and Young’s modulus of the treated cotton fibers increase slightly. It is also a possible way to achieve saltfree dyeing with reactive dyes. Several researches concluded that when poly(amidoamine) increases in cellulose fiber, the mechanism of dye adsorption changes from Freundlich to Langmuir model. Moreover, dendritic polymers can be used as a template for inorganic nano-particles. Both poly(amidoamine) silver salts and nano-composites can display antimicrobial activity. On the other hand, the water and oil repellency results showed that poly(amidoamine) dendrimer containing fluorocarbon had better results than conventional ones in relation to performance and washing resistance. To improve wash and wear properties, poly(amidoamine) dendrimers can be modified and applied as a new material for wrinkle resistance of cotton.
Keywords: flame retardant